Food Habits of Green Lobster (Panulirus Homarus) Fed with Calcium- and Phosphorus-Rich Feed Observed Using Artificial Intelligence “Smart Lobster-Culture” - Rita Rostika; Kiki Haetami; Alexander Khan; Buntora Pasaribu; M. Ikhsan C.U; Lady Ayu Sri Wijayanti (International Journal Labs, 2025)
This study aims to investigate the food habits of green lobsters (Panulirus Homarus) when fed with natural feed rich in calcium and phosphorus, and to assess their growth performance, survival rate, and water quality in relation to different feeding treatments. The research was conducted in 2024 at the Marine Station of Pangandaran University, located in Pangandaran Regency. The study utilized a Complete Random Design (RAL) with four different feeding treatments over 6 x 10 days: A (80% anchovy feeding), B (100% anchovy feeding), C (80% rebon feeding), and D (100% rebon feeding). The parameters observed include Growth Rate based on Length (LPP) and Weight (LPB), Survival Rate (SR), and Water Quality. Additionally, natural feed habits were monitored using the AI Smart Lobster Culture version 1. The results showed that lobsters fed with 100% anchovy and rebon (treatments B and D) exhibited the highest weight increase, with values of 61.4 and 65.1, respectively, while treatments A and C showed no significant differences. The Survival Rate (SR) across all treatments (A, B, C, and D) was excellent, with an SR of 96%. The findings indicate that both anchovy and rebon, rich in calcium and phosphorus, are effective in supporting lobster growth and survival. In conclusion, this study demonstrates that feeding green lobsters with 100% calcium and phosphorus-rich feed, such as anchovies and rebon, promotes optimal growth and survival, highlighting the importance of feed composition in lobster culture.